Development of a validated RP-HPLC assay method for quantitative separation of Teriflunomide and its process-related impurities in bulk drugs - Bhagavan Rajesh Babu Koppisetty, Rajendra Prasad Yejella, A. Krishna Manjari Pawar, Srinivasa Rao Yarraguntla, Varaprasada Rao Kollabathula, Vasudha Dadi, Challa Gangu Naidu (Journal of Applied Pharmaceutical Science, 2023)
The organic, inorganic, and residual solvent impurity sources in pharmacological compounds have been divided into categories by the International Council for Harmonization. The pharmaceutical sector faces a regulatory hurdle since the organic contaminants could be genotoxins. The detection and method development also a validation of organic contaminants produced during the chromatographic separation of a teriflunomide is the main goal of this work. The impurity profile research was carried out using a diode array detector and reverse phase-high performance liquid chromatography. At a column temperature of 25°C, the C18 YMC-Pack ODS column was successfully achieved through gradient separation. As the mobile phase, acetonitrile and 0.015 M potassium dihydrogen phosphate with a pH of 3.5 were employed. A 210 nm detector wavelength and 1.0 ml/minute flow rate were adopted. Six process-related impurities were successfully separated using the validated analytical method, with resolution and retention times under 35 minutes. Teriflunomide, Teriflunomide stage-1, and Impurity-D have established analytical techniques with ranges of 0.066–3.262, 0.035–1.880, and 0.025–1.255 μg/ml, respectively. Teriflunomide, Teriflunomide stage-1, and impurity-D have respective limits of detection and limit of quantification values of 0.0037 and 0.0096, 0.0016 and 0.0051, and 0.0011 and 0.0033 μg/ml. The confirmed analytical approach can effectively identify any manufacturing process impurities.